(untitled) (Archives of Criminology, 2012)
Despite dramatic social changes and unprecedented technological innovations penal philosophy has undergone little change. Retribution continues to be the key principle in sentencing and judges continue their hopeless struggle to make the punishment fit the crime. It is truly baffling that the CJS has remained archaic in its philosophy, its outlook and its tools and has remained insulated from whatever changes and advances that had taken place in modern society? For as yet unexplained reasons the system has resisted every attempt to modernize and change? This is probably why it is that despite the manifest advantages and benefits of R.J. over a punitive, retributive system, whose sole aim is to inflict pain and suffering on the wrong-doer, there is still reluctance to do away with the ideas of expiation and penitence in favor of reconciliation and compensation. The strong support for victims of crime, coupled with the undeniable fact that victims are the main losers in a punitive system of justice, have not yet succeeded in convincing politicians, lawmakers or the general public of the need to replace the medieval practice of punishment by a more constructive, more peaceful and less harmful means of dealing with crime and conflict. And yet, the destructive and detrimental effects of punishment are too evident to ignore. All this suggests that the time is right for a paradigm shift in society’s response to crime. There is a desperate need to move from philosophical abstraction to restorative action, from senseless retribution to meaningful restitution, from just deserts to restorative justice. But there is also a need for realism. R.J. is not a pana-cea. Although superior in every respect to retribution R.J. does have certain limitations and there are certain dangers to be avoided when moving towards the full implementation of a restorative justice system.